CARDIOVASCULAR RISK AMONG MEN OF WORKING AGE WITH ARTERIAL HYPERTENSION DEPENDING ON THE ARTERIAL PRESSURE DIURNAL PROFILE - Nataliia M. Pryplavko; Anatolii M. Kravchenko (Клінічна та профілактична медицина, 2023)
Aim: to investigate the relationship between cardiovascular risk (CVR) and different types of diurnal blood pressure (BP) profile among men of working age with arterial hypertension (AH).